2016
DOI: 10.1103/physrevb.94.174110
|View full text |Cite
|
Sign up to set email alerts
|

Phase coexistence and pinning of charge density waves by interfaces in chromium

Abstract: We study the temperature dependence of the charge density wave (CDW) in a chromium thin film using x-ray diffraction. We exploit the interference between the CDW satellite peaks and Laue oscillations to determine the amplitude, the phase and the period of the CDW. We find discrete half-integer periods of CDW in the film and switching of the number of periods by one upon cooling/heating with a thermal hysteresis of 20 K. The transition between different CDW periods occurs over a temperature range of 30 K, sligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…This is also consistent with the observed decrease in correlation lengths of orbitally-ordered domains from 17 nm to 6 nm with a normalized integrated peak intensity drop of 80% to 10% near 100 K. In this phase separation regime, the metallic/insulating interface leads to the pinning of the trimeron chains, resulting in a slowdown of orbital fluctuation timescales. Pinning of charge density waves by an interface has been previously observed in other correlated systems [24].…”
supporting
confidence: 52%
“…This is also consistent with the observed decrease in correlation lengths of orbitally-ordered domains from 17 nm to 6 nm with a normalized integrated peak intensity drop of 80% to 10% near 100 K. In this phase separation regime, the metallic/insulating interface leads to the pinning of the trimeron chains, resulting in a slowdown of orbital fluctuation timescales. Pinning of charge density waves by an interface has been previously observed in other correlated systems [24].…”
supporting
confidence: 52%
“…In comparison to our previous study of the same sample at cryogenic temperatures [13], the CDW observed here at room temperature has a lower spatial frequency and reduced amplitude, which are shifted by an amount consistent with previous studies [24]. We want to stress that previous works by Singer et al studied this same Cr sample [13,25,26], focusing exclusively on the CDW, and for that reason we do not include a more in-depth discussion of this mechanism here.…”
supporting
confidence: 91%
“…The amplitudes can be fit well with a Gaussian (as used to model the Laue fringe envelope from surface roughness in Ref. [26]) summed with a Lorentzian for the CDW (a Gaussian CDW peak gives a slightly lower quality fit). An important feature of the data is the reduced amplitude of the oscillations that occurs after about 4 ps (see Fig.…”
mentioning
confidence: 99%
“…The high Néel temperatures (311 K in bulk 3 , decreased due to dimensional crossover 10 to 290 ± 5 K in the 28 nm film studied here 11 , 12 ) render the critical behaviour close to the SDW phase transition highly accessible. Thin antiferromagnetic films with SDW states are especially important for devices utilizing spin transport 13 , 14 and sustain a unidirectional SDW and discrete SDW periods due to pinning at the interfaces 15 , 16 . The magnetostrictive coupling between SDW and PLD allows for the excitation of acoustic phonons by fully or partially quenching the SDW order parameter throughout the film with a photoexcitation 17 19 .…”
Section: Introductionmentioning
confidence: 99%